Penerapan Kurikulum 2013 Pada Masa Pandemi COVID-19 di SMP IT Ad-Durrah Medan - Saddan Yasir; Hamidah Hamidah; Putri Dewi Anggia (Al-Ulum: Jurnal Pendidikan Islam, 2020)
This study aims to analyze the application of the 2013 Curriculum during the COVID-19 pandemic. This research was carried out at SMP IT Ad-Durrah Medan. The research method used is a qualitative method, with a descriptive study model. The results of the study show that the implementation of the 2013 Curriculum during the COVID-19 pandemic at SMP IT Ad-Durrah Medan still carries out learning, but is done remotely based on an internet network. Policies are carried out by following government regulations. The implementation has an impact, namely: 1) graduate competence is not achieved, 2) attitudinal competence is not achieved, 3) routine student activities are not carried out. The obstacles faced are: 1) the difficulty of students understanding learning, 2) there are parents of students who cannot provide learning facilities, 3) cannot do simultaneous learning, 4) cannot optimally review student development. A review of the results of the assessment which includes the assessment of attitudes, knowledge and skills has decreased. The decline was due to the holding of distance learning, so that schools had difficulty developing the three aspects to be achieved.Keyword : curriculum2013, islamic school, pandemic Covid-19